Association of MCP-1 rs1024611 polymorphism with diabetic foot ulcers. Issue 28 (July 2018) - Su, Na; Zhao, Nairui; Wang, Guangya; Wang, Linxia; Zhang, Yunna; Li, Ruijie; Liu, Ying; Yang, Xinxin; Li, Cuiliu; Hou, Mingming
Abstract : Abstract: Monocyte chemotactant protein-1 ( MCP-1 ), a pro-inflammatory cytokine, plays an important role in inflammatory process. In present study, we evaluated the association of MCP-1 gene rs1024611 polymorphism with risk and clinical characteristics of diabetic foot ulcers (DFUs). This study recruited 116 patients with DFUs, 135 patients with diabetes mellitus (DM) without complications (non-DFU), and 149 healthy controls (HCs). MCP-1 gene rs1024611 polymorphism was genotyped by direct sequencing. The expression of MCP-1 was analyzed using quantitative real-time polymerase chain reaction. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assume the association strength. Individuals with rs1024611 AG and GG genotypes exhibited significantly higher susceptibility to DFUs, in the comparison with HCs (AG vs AA, OR = 2.364, 95% CI = 1.021–5.470; GG vs AA, OR = 2.686, 95% CI = 1.154–6.255). Meanwhile, G allele was associated with increased DFUs susceptibility (OR = 1.457, 95% CI = 1.014–2.093). Besides, rs1024611 SNP was slightly correlated with increased DFUs susceptibility in patients with DM. GG genotype of rs1024611 was significantly correlated with higher epidermal thickness and lower dermis thickness in patients with DFUs ( P < .01). Patients with DFU exhibited upregulation of MCP-1 mRNA, and GG genotype was correlated with enhanced MCP-1 expression in DFU and non-DFU groups. Rs1024611 polymorphism was significantly associated with MCP-1 expression and individual susceptibility to DFUs.